Monitoramento SNMP para avaliar a qualidade das chamadaas em um ambiente VoIP - Lima, Ana Flávia Marinho de (2006)
The voice transmission over the IP network is gaining every day more users, ease of use and cost reduction on calls. Voice over IP, or simply VoIP is an application that transmits voice bundled with the IP (Internet Protocol). In VoIP, voice is transmitted in an IP packet network, which has become a challenge with regard to the quality of calls because the IP network is not suitable to carry packages in real time, since its operation is based If the best efiort, that is, at best effort. Because of this feature, the IP network does not guarantee reliable delivery of packets to their destination. Studies on call quality in VoIP networks are very relevant, because this is a key factor to win the user which in turn, is increasingly demanding. With the increasing development of new applications such as voice over IP, the management task becomes critical to maintain the proper functioning of the network and consequently ensure the satisfaction of usurers. This paper aims to present a scenario based on the SNMP management model (Simple Network Management Protocol) to monitor the behavior of factors such as losses and delays that degrade call quality and measuring quality of these calls on a VoIP network . monitor the behavior of these factors and the result of the quality of the calls keep the network administrator informed periodically about this information and, consequently, would provide the degree of user satisfaction. It has also the objective to develop an application that implements the proposed scenario, this scenario consists of five entities such as VoIP applications, tool collection, Statistical Daemon, and Agent Manager. The description of information that make up the agent database and the description of the Statistical Daemon configuration file are available in the Appendices. The source code of the application monitoring is all open source and is at the Federal University of Ceará -UFC. Other researchers from the UFC are using the application developed here to assist them in developing new research on voice over IP.